A Scoping Review of Safety and Health Interventions in the High-Risk Dairy Industry: Gaps in Evidence Point to Future Directions in Research. Issue 1 (2nd January 2022) - Driscoll, Maryellen; Dalton, Deborah; Jenkins, Paul; Tinc, Pamela; Murphy, Dennis; Douphrate, David I.; Lundqvist, Peter; Pate, Michael; Lindahl, Cecilia; Meyerhoff, Anna; Scott, Erika; Carrabba, James; et al.
ABSTRACT: The occupational injury rate of the dairy industry (6.6 per 100 full-time workers) is twice that of the national average across all industries (3.3 per 100 full-time workers). While dairy farms are becoming larger in size and fewer in number, this rate has not changed. A scoping review was conducted to identify published reports of occupational safety interventions in the dairy industry. An additional criterion was that the study included an evaluation of the intervention. Out of 22 articles that met the first criterion (discussion of interventions specific to the dairy industry), 19 met the second of having an evaluative component. These 19 articles corresponded to 16 unique studies, because 4 articles corresponded to the same study. Of the 16 unique studies, only 3 had a comparison of treatment vs. control effects, and none measured the impact of the intervention on injuries and fatalities. Of the 16 interventions, 6 were focused on training or informational campaigns in which the evaluations primarily measured knowledge acquisition. Additionally, none of these studies had a sufficient sample size to compare injury rates as an outcome. Our study demonstrates that the literature lacks any rigorous evaluation of whether dairy safety interventions are making an impact on injury prevention. Given this, it is not possible to determine how work-related injuries and deaths can be prevented in the dairy industry. Recommendations for future research include incorporating rigorous evaluation into research designs and attempting to develop low-cost, unobtrusive methods for collecting data on intermediate and final outcomes.